IN GEOGRAPHY EDUCATION IN SECONDARY SCHOOLS IMPROVING THE MECHANISMS OF FORMING STUDENTS' GEOECOLOGICAL CULTURE - Abdullaeva Dilnoza Narzullaevna; Qo‘ldoshev Foziljon (Journals Park Publishing, 2023)
This article is devoted to the theoretical study of issues related to the process of formation of geoecological culture through school geography education. The authors, expressing the opinions and comments obtained as a result of their scientific research, tried to determine the prospective study vector of the problem.
Keywords: sustainable development, geography, ecology, geoecology, geoecological system, methodology.